Rhizobial inoculation in black wattle plantation (Acacia mearnsii De Wild.) in production systems of southern Brazil - Monteiro, Pedro Henrique Riboldi; Kaschuk, Glaciela; Winagraski, Etienne; Auer, Celso Garcia; Higa, Antônio Rioyei (Brazilian journal of microbiology, 2019)
Black wattle ( Acacia mearnsii De Wild.) is a tree legume native to southeast Australia, but present in all continents. Today it covers about 142,400 ha in Brazil, with plantations concentrated in the southern region of the country. Black wattle may form nodules and establish rhizobial symbiosis capable of fixing N 2 , but rhizobial inoculation is not done in commercial plantations. About 40 kg ha −1 of urea is applied during seedling transplantation. In this review, evidences by which rhizobial inoculation affects monoculture, mixed cultivation, and agroforestry black wattle production systems were searched in literature. Previous measurements in cultivated forests have indicated that biological nitrogen fixation in black wattle may provide up to 200 kg of N ha −1 year −1 to the soil. Therefore, rhizobia inoculation may bring several opportunities to improve black wattle production systems. Black wattle is not a very selective partner in the rhizobial symbiosis, but the genus Bradyrhizobium dominates the rhizobial diversity of black wattle nodules. Investigation on rhizobial diversity in soils where the crop is cultivated may represent an opportunity to find more effective rhizobia strains for inoculants. The successful history of biological nitrogen fixation in grain legumes must inspire the history of tree legumes. Microbiology applied to forestry must overcome challenges on the lack of trained professionals and the development of new application technologies.